2017
DOI: 10.3892/ol.2017.7517
|View full text |Cite
|
Sign up to set email alerts
|

Family with sequence similarity 83, member�B is a predictor of poor prognosis and a potential therapeutic target for lung adenocarcinoma expressing wild‑type epidermal growth factor receptor

Abstract: Lung adenocarcinoma (ADC) patients with tumors that harbor no targetable driver gene mutation, such as epidermal growth factor receptor (EGFR) gene mutations, have unfavorable prognosis, and thus, novel therapeutic targets are required. Family with sequence similarity 83, member B (FAM83B) is a biomarker for squamous cell lung cancer. FAM83B has also recently been shown to serve an important role in the EGFR signaling pathway. In the present study, the molecular and clinical impact of FAM83B in lung ADC was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In addition to the evaluation of FAM83 expression in tumor tissue, functional assays were performed in several NSCLC cell lines. In agreement with previous studies, FAM83A and B depletion had a significant effect on the proliferation and AIG of ADC cells [8,9,27]. We were able to show that downregulation of FAM83A resulted in impaired migration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to the evaluation of FAM83 expression in tumor tissue, functional assays were performed in several NSCLC cell lines. In agreement with previous studies, FAM83A and B depletion had a significant effect on the proliferation and AIG of ADC cells [8,9,27]. We were able to show that downregulation of FAM83A resulted in impaired migration.…”
Section: Discussionsupporting
confidence: 92%
“…Because of its involvement in PI3K/Akt and MAPK signaling, FAM83B has also been shown to confer a decreased sensitivity to PI3K, Akt, and mTOR inhibitors in immortalized human mammary epithelial cells [13]. In lung ADC, FAM83B expression has been shown to be significantly elevated in tumors with wild-type EGFR [27], while in our patient samples, a significant difference was not observed. Here again, differences in quantification methods might be responsible for the divergent results.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…To better elucidate the role of FAM83B in the maintenance of thyroid cell differentiation and in cell migration, we performed silencing experiments using two different siRNAs 11 in the two cell lines, NTHY-ORI and TPC1, which expressed high FAM83B levels. We found that the knock down of FAM83B significantly affect normal and tumor thyroid cell differentiation, inducing in NTHY-ORI a reduction in the expression of the thyroid marker genes PAX8 and NIS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Family with sequence similarity 83, member B ( FAM83B ) is reported to be a novel molecule involved in the development of various malignant tumors, including pancreatic ductal Adenocarcinoma ( 10 ) and gastric cancer ( 11 ). Previous studies have demonstrated that FAM83B can directly activate the PI3K/AKT/mTOR signaling pathway in tumors, including breast, lung, ovarian and cervical cancer, by binding to PI3K ( 12 , 13 ) or can indirectly activate the pathway by binding and hyper-activating EGFR in lung adenocarcinoma ( 14 ). Our previous study demonstrated that FAM83B knockdown inhibits endometrial cancer cell proliferation and metastasis through the inhibition of the PI3K/AKT/mTOR signaling pathway ( 15 ).…”
Section: Introductionmentioning
confidence: 99%